Children in Digital Age – Slovenian Perspective - Lesjak, Benjamin (Children in Digital Age, 2025)
Abstract:This country report explores the use and impact of digital devices among Slovenian children and adolescents, along with the Slovenian legal framework concerning children’s rights, specifically in the context of digital services and social media. It reveals that smartphones are the most used devices among Slovenian youth, with significant hours spent on them daily. Television and computers are also commonly used, though less so than smartphones. The influence of parents in guiding technology use and the popularity of various social networks among different age groups are highlighted. Legal definitions of a child and minor, as well as the role of parents, are explored within the Slovenian legal system. The document further examines Slovenia’s stance on children’s rights in the digital era, emphasising the lack of a specific law for children’s rights while acknowledging the Constitution and Family Code’s role in ensuring their protection. The role of public institutions, legal remedies, and education in safeguarding children in the digital space is also examined, highlighting the contributions of various organisations and legal acts in promoting safe internet use and protecting children’s rights online. The abstract underscores the complexity and evolving nature of children’s digital rights, emphasising the need for continued vigilance and adaptation to protect these vulnerable members of society. Keywords: digital device usage, Slovenian adolescents, legal framework, children’s rights, online content regulation